Air concentration and bubble characteristics downstream of a chute aerator. (December 2016) - Bai, Ruidi; Zhang, Faxing; Liu, Shanjun; Wang, Wei
Highlights: This study investigated the lower jet independently and completely avoided interference with the upper aeration. Large amount of air entrained in the cavity zone was only partially entrained into the exiting flow. In the impact zone, the air concentration decreased sharply while the air bubble frequency decreased to a lesser extent. In the equilibrium zone of the air-water cross-section, the range of probability of bubble chord lengths tended to increase from the bottom to the upper surface. The distributions of the mean chord lengths followed approximately a power law distribution. Abstract: Chute aerators separate the flow of water from the bottom of a chute, and air bubbles generated in the cavity zone must go through the impact zone as they travel downstream. In this study, the air concentration and air bubble characteristics along the chute were investigated systematically by a series of model tests that eliminated the effect of the upper aeration region. It was found that the large amount of air entrained in the cavity zone was only partially entrained into the final flow. Based on the lower air discharge properties, the chute downstream of the aerator was partitioned into four reasonable zones: the cavity zone (0 < x < L ), the impact zone ( L ≤ x ≤ Lm ), the equilibrium zone ( Lm ≤ x ≤ LD ), and the far zone (x > LD ). The details of the bubble chord length and bubble frequency distributions in each zone were measured. In the cavity zone, the bubble frequency distribution was related to the air concentration by a parabolic law. In the impact zone, the air concentration decreased sharply while the bubble frequency decreased to a lesser extent. Due to the turbulent fluctuation effect, the probability of smaller bubbles increased while the probability of larger bubbles decreased as they progressed down the chute. In the equilibrium zone, the bubble frequency decreased slightly. At the cross section, the range of probability of bubble chord lengths tended to increase from the bottom to the upper surface. The distributions of the mean chord lengths followed approximately a power low distribution. A formula was provided to predict the maximum air bubble frequency in the impact and equilibrium zones.